IMPLEMENTATION OF COMMUNITY EMPOWERMENT PROGRAMS USING VARIOUS VILLAGE FUND SOURCES IN BAGAN MELIBUR MERANTI ISLANDS REGENCY - Wan Jumiati; Sufian Hamim; Hamdi Agustin (RADJA PUBLIKA, 2025)
The purpose of this study is to analyze and explain the Implementation of the Community Empowerment Program from Various Sources of Village Funds in Bagan Melibur, Meranti Islands Regency. The theory used in this study is the Empowerment theory of Aprilia Theresia, et al. (2014) and Team Work Lapera (2001) which emphasizes several limitations of empowered village communities, namely: welfare problems, problems of access to resources, problems of awareness, the ability to understand the problems faced; and participation problems. The nature of this study is qualitative with a descriptive analytical type. The number of informants was 17 people through purposive sampling techniques. Data collection techniques were by interviews and observations. The results of the study showed that the implementation of the community empowerment program from various sources of village funds was not yet effective, because at the preparation stage there was no provision of expert assistants, lack of data and information about the state of village potential related to the productive economic community empowerment program. Community empowerment has not been optimal due to lack of access to capital and mentoring and training. Lack of assistance and provision of agricultural mechanization, superior seed technology, fertilizers, pesticides, and others, which are needed by farmers. The poor performance of BUMDES and Village Cooperatives and the lack of partnerships with private companies in both production and marketing of products. Incorporating a cultural approach in the implementation of community empowerment programs in Bagan Melibur is essential to align development initiatives with local values, traditions, and social norms, thereby enhancing community participation and ownership. This approach leverages existing social cohesion and indigenous knowledge to overcome challenges related to resource access, awareness, and institutional performance, ultimately fostering more sustainable and effective empowerment outcomes.